Heme Oxygenase-2 Modulates Early Pathogenesis after Traumatic Injury to the Immature Brain - Yoneyama-Sarnecky, Tomoko (S. Karger AG, 2010)
We determined if heme oxygenase-2 (HO-2), an enzyme that degrades the pro-oxidant heme, confers neuroprotection in the developing brain after traumatic brain injury (TBI). Male HO-2 wild-type (WT) and homozygous knockout (KO) mice at postnatal day 21 were subjected to TBI and euthanized 1, 7, and 14 days later. Relative cerebral blood flow, measured by laser Doppler, cortical and hippocampal pathogenesis, and motor recovery were evaluated at all time points. Cerebral blood flow was found to be similar between experimental groups. Blood flow significantly decreased immediately after injury, returned to baseline by 1 day, and was significantly elevated by 7 days, post-injury. Nonheme iron preferentially accumulated in the ipsilateral cortex, hippocampus, and external capsule in both WT and KO brain-injured genotypes. There were, however, a significantly greater number of TUNEL-positive cells in the hippocampal dentate gyrus and a significantly greater cortical lesion volume in KOs relative to WTs within the first week post-injury. By 14 days post-injury, however, cortical lesion volume and cell density in the hippocampal CA3 region and dorsal thalamus were similar between the two groups. Assays of fine motor function (grip strength) over the first 2 weeks post-injury revealed a general pattern of decreased strength in the contralateral forelimbs of KOs as compared to WTs. Together, these findings demonstrate that deficiency in HO-2 alters both the kinetics of secondary damage and fine motor recovery after TBI.